Long-term CO₂ injection and its impact on near-surface soil microbiology - Gwosdz, Simone; West, Julia M.; Jones, David; Rakoczy, Jana; Green, Kay; Barlow, Tom; Blöthe, Marco; Smith, Karon L.; Steven, Michael D.; Krüger, Martin (Oxford University Press, 2016)
Impacts of long-term CO₂ exposure on environmental processes and microbial populations of near-surface soils are poorly understood. This near-surface long-term CO₂ injection study demonstrated that soil microbiology and geochemistry is influenced more by seasonal parameters than elevated CO₂. Soil samples were taken during a 3-year field experiment including sampling campaigns before, during and after 24 months of continuous CO₂ injection. CO₂ concentrations within CO₂-injected plots increased up to 23% during the injection period. No CO₂ impacts on geochemistry were detected over time. In addition, CO₂ exposed samples did not show significant changes in microbial CO₂ and CH₄ turnover rates compared to reference samples. Likewise, no significant CO₂-induced variations were detected for the abundance of Bacteria, Archaea (16S rDNA) and gene copy numbers of the mcrA gene, Crenarchaeota and amoA gene. The majority (75%–95%) of the bacterial sequences were assigned to five phyla: Firmicutes, Proteobacteria, Actinobacteria, Acidobacteria and Bacteroidetes. The majority of the archaeal sequences (85%–100%) were assigned to the thaumarchaeotal cluster I.1b (soil group). Univariate and multivariate statistical as well as principal component analyses showed no significant CO₂-induced variation. Instead, seasonal impacts especially temperature and precipitation were detected.